Study of the Effect of Saw Gin Raw Material Roller Density on Fiber Quality Indicators - Student R.Z.Uralov; Docent A.P.Mavlyanov; Docent A.A.Umarov (Zien Journals, 2023)
In the article is analyzed the technological process in the working chamber of the saw gin. Based on the data on the density and kinematics of the raw roller, the interaction of the saw and the raw roller is shown. The reasons for the formation of ginning defects in the fiber are shown
Keywords: saw gin; raw roller; density; fiber quality index